PENGARUH STRESS KERJA, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KOPERASI KONSUMEN KARYAWAN PT PLATINUM CERAMIC INDUSTRY KARANG PILANG - Febriana, Sela; Ilmi, Nurul; nurna dewi, nuning (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2025)
The purpose of this study is to examine the effect of work stress, work motivation, and work discipline on the performance of employees at PT Platinum Ceramic Industry's employee consumer cooperative. The population in this study was all employees of PT Platinum Ceramic Industry's employee consumer cooperative, while the sample used by the researcher consisted of 47 people. The sampling technique used is non-probability sampling with a saturated sample technique. The data analysis technique uses SPSS 24.0. The findings of the t-test show that work stress (X1) has a negative and insignificant effect on employee performance at the Consumer Employee Cooperative of PT Platinum Ceramic Industry, while work motivation (X2) has a positive and significant effect on employee performance at the Employee Consumer Cooperative of PT Platinum Ceramic Industry, and work discipline (X3) has a positive and significant effect on employee performance at the Employee Consumer Cooperative of PT Platinum Ceramic Industry. Furthermore, the findings of the F-test for work stress (X1), work motivation (X2), and work discipline (X3) simultaneously have a positive and significant effect on employee performance at the Employee Consumer Cooperative of PT Platinum Ceramic Industry. Keyword : Work Stress, Work Motivation, Work Discipline and Employee Performance